Abdominal Trauma by Impalement. Clinical Case - Flores-López, Alejandro Alberto; Pinzón-Oregón, Onasis; Falcón-Cancino, Luis Arturo; Yépez-Vallejo, Segundo; Ríos-Pacheco, Mónica; Lujan-Vargas, Héctor Gerardo; Echavarría-Fernández, Fidel; Padrón-Arredondo, Guillermo; Villalobos-Rodríguez, Alejandro L. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Impalement injury is one of the most spectacular and potentially dramatic rare forms of penetrating trauma. [2,3] In many cases, the impaled patient dies at the scene.[3] The patient who manages to reach the hospital alive and is hemodynamically stable has a good chance of overcoming a traumatic event. However, the non-removal of a foreign object represents the cornerstone of initial treatment, as possible vascular lesions remain compressed by the object in situ, thus avoiding irrepressible hemorrhages. Clinical case: A 32-year-old male was brought in by a paramedic after suffering electrical burns to the right thoracic limb and right pelvic limb that caused a fall from a power pole with subsequent penetrating abdominal trauma due to impalement. He denies antecedents of importance for the current condition. Upon arrival, he was hemodynamically stable, with the presence of a first-degree electrical burn in the right hand and forearm and the right thigh, as well as a metallic rod passing through the abdomen from the left groin to the right flank, for which it was decided to perform Exploratory Laparotomy who reported the following findings: Intestinal perforation of more than 50% of the lumen at jejunum level, side-to-side anastomosis was performed. During his stay on the floor of General Surgery, he had a torpid post-surgical evolution, intolerance to the oral route, abdominal distension, absence of gas channeling, and symptoms of intestinal obstruction, for which it was decided to perform a new Exploratory Laparotomy, finding intestinal stenosis at the level of the previous anastomosis was dismantled and reconstructed in side by side, on this occasion with favorable evolution and he was discharged due to improvement after 14 days of hospital stay. Discussion: Prehospital emergency medicine (PHEM) offers unique and challenging perspectives to orthodox emergency medicine. Impalements are extremely rare and often require a multidisciplinary team approach in the prehospital setting. Most cases of impalements are fatal at the scene. Patients surviving the initial trauma and arriving at the hospital alive, usually make a good recovery with multidisciplinary team management underpinning the importance of meticulous prehospital care in transporting patients with impalements safely. This case highlights the role of PHEM clinicians as experts in clinical knowledge, decision-making, leadership, team working skills, and improvisations.